TEXTILE INDUSTRY AWARENESS CONCERNING THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY: A CASE STUDY OF THREE TEXTILE PLANTS IN BANDUNG AREA - Sukapto, Paulus; Djojosubroto, Harjoto (LIPI Press, 2013)
The present study explores awareness concerning the implementations of occupational safety of three textile plants in Bandung area. The study was supported by data from our visit to those respective textile plants, i.e. from discussions with the managers and employees, the observations towards the working conditions and the activities of the employees, and the response of questionnaires asked to the operators. It was found that the occupational safety procedures have to be improved. The lighting levels in most departments of these plants shall be higher than the present lighting level. The noise levels in two of the three plants have to be lowered. Out of the questionnaire it was learned that the adverse effects of the poor workplace conditions were experienced by the employees. The safety organization of these plants was not integrated to the organizational structure of the respective company. Among those three textile plants, only one plant provided data on accidents in 2011 and 2012. It seems that the number and the severity of the accidents were not signifi cantly different. In 2012 there was an accident that led to permanent disability. The awareness and the concern of the managers to the occupational safety were poor. That is why it is proposed that the occupational safety solutions of these plants have to be performed by safety management approach based on macro-ergonomics principles.